2011
DOI: 10.1108/13552551111107507
|View full text |Cite
|
Sign up to set email alerts
|

Self‐regulation and effort in entrepreneurial tasks

Abstract: PurposeThe central question of this paper is, “What determines an entrepreneur's effort on different tasks?” The paper aims to address this question.Design/methodology/approachPropositions about the impact cognitive processes have on entrepreneurial effort across different tasks are developed. These propositions draw on self‐regulatory theory, in particular our understanding of regulatory focus and self‐efficacy.FindingsIt is argued that a promotion orientation motivates effort on explorative tasks, and a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 141 publications
(169 reference statements)
3
45
0
2
Order By: Relevance
“…Such finding is correspondent with the results of previous research (Barbosa et al, 2007;BarNir et al, 2011;Carr & Sequeira, 2007;Kickul et al, 2009;Liñán, 2008;Piperopoulos & Dimov, 2015;Sesen, 2013;Trevelyan, 2011;Zhao et al, 2005). As social cognitive theory claims, no mechanism of personal agency is more central or pervasive than beliefs of self-efficacy (Bandura, 1989).…”
Section: Cyber-entrepreneurial Self-efficacy Has a Direct Positive Efsupporting
confidence: 81%
See 1 more Smart Citation
“…Such finding is correspondent with the results of previous research (Barbosa et al, 2007;BarNir et al, 2011;Carr & Sequeira, 2007;Kickul et al, 2009;Liñán, 2008;Piperopoulos & Dimov, 2015;Sesen, 2013;Trevelyan, 2011;Zhao et al, 2005). As social cognitive theory claims, no mechanism of personal agency is more central or pervasive than beliefs of self-efficacy (Bandura, 1989).…”
Section: Cyber-entrepreneurial Self-efficacy Has a Direct Positive Efsupporting
confidence: 81%
“…Commitment can be accompanied by different ways of thinking that plays a role in shaping behavior and may even lead to the persistence to a course of action, even in the face of conflicting motives or attitudes (Meyer & Herscovitch, 2001). ESE has a high degree of influence over the entrepreneurial intention of and the extent of effort made by a potential entrepreneur; and it affects his/her willingness to withstand the changes and challenges they encounter during the entrepreneurial process in order to become a successful entrepreneur (Trevelyan, 2011).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…In general, higher selfefficacy is associated largely with higher performance (Bandura 2006). Entrepreneurs with high ESE were theorized to perform better than their peers because of setting more challenging goals, investing more effort to achieve those goals, and being more persistent when meeting obstacles (e.g., Markman et al 2002;Trevelyan 2011). However, in a meta-analysis of 26 studies, Miao et al (2017) found only a moderate correlation (0.309) between ESE and company performance, with several pieces of research ascertaining a weak or even negative relationship.…”
Section: The Evolution Of Ese Ese-growth Expectations and Ese-actuamentioning
confidence: 99%
“…New business phase entrepreneurs are those former nascent entrepreneurs who have been in business for more than 3 months, but less than 3.5 years (Herrington & Kew 2017;Turton & Herrington 2012). New business entrepreneurs are owning and managing a business, implementing the business plan, running the business on day-to-day basis, planning for growth, innovation, implementing organisational systems and hiring employees (Man, Lau & Chan 2002;Trevelyan 2011). …”
Section: Literature Review Entrepreneurship Phasesmentioning
confidence: 99%
“…Established entrepreneurs are focused on owning and managing a business, environmental scanning for new opportunities, quality control, evaluating ideas with existing frameworks, refining existing production processes, creating organisational structures to speed up production, creating new products and provision of a more stable base of employment (Man et al 2002;Herrington & Kew 2017;Trevelyan 2011). While nascent and new business entrepreneurs contribute to dynamism and innovation in an economy, established businesses and their owner-managers often provide stable employment and exploit the knowledge and social capital accumulated in past experiences (Amorós & Bosma 2014).…”
Section: Literature Review Entrepreneurship Phasesmentioning
confidence: 99%